2022
DOI: 10.1093/neuonc/noac146
|View full text |Cite
|
Sign up to set email alerts
|

Management of neurofibromatosis type 1-associated plexiform neurofibromas

Abstract: Plexiform Neurofibromas (PN) are a common manifestation of the genetic disorder neurofibromatosis type 1 (NF1). These benign nerve sheath tumors often cause significant morbidity, with treatment options limited historically to surgery. There have been tremendous advances over the past two decades in our understanding of PN, and the recent regulatory approvals of the MEK inhibitor selumetinib are reshaping the landscape for PN management. At present, there is no agreed upon PN definition, diagnostic evaluation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 108 publications
0
48
0
Order By: Relevance
“…The phase 1 and 2 clinical trials with the MEKi selumetinib for children with inoperable symptomatic PNs resulted in a partial response in 71% and 74% of patients, respectively. 1 It was also seen that the patients also experienced less pain and improved function and quality of life while on treatment which was significant. Thus, selumetinib became the first medical drug of choice to be approved by the FDA for the management of PNs in children.…”
Section: Medical Management With Mitogen-activated Protein Kinase Inh...mentioning
confidence: 84%
See 1 more Smart Citation
“…The phase 1 and 2 clinical trials with the MEKi selumetinib for children with inoperable symptomatic PNs resulted in a partial response in 71% and 74% of patients, respectively. 1 It was also seen that the patients also experienced less pain and improved function and quality of life while on treatment which was significant. Thus, selumetinib became the first medical drug of choice to be approved by the FDA for the management of PNs in children.…”
Section: Medical Management With Mitogen-activated Protein Kinase Inh...mentioning
confidence: 84%
“…However, in the past two decades, the Mitogen-activated protein kinase (MEK) inhibitor selumetinib is showing promising treatment of PNs. 1 The incidence of Neurofibromatosis'(NF 1) type 1 (von Recklinghausen NF) occurs in 1 of 4000 births and is inherited in an autosomal dominant pattern with variable penetrance. Spontaneous mutation occurs in 50% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…Several other MEK inhibitors (i.e., trametinib) have also shown efficacy or are in testing in phase II trials for both pediatric and adult patients with NF1 38 . These targeted agents have been shown to reduce tumor size, slow neoplastic growth, and may prevent worsening of spinal cord compression 39–41 . One expert reported that within their institution, there is currently movement toward recommending MEK inhibitors before performing surgery, when possible, for spinal neurofibromas.…”
Section: Discussionmentioning
confidence: 99%
“…38 These targeted agents have been shown to reduce tumor size, slow neoplastic growth, and may prevent worsening of spinal cord compression. [39][40][41] One expert reported that within their institution, there is currently movement toward recommending MEK inhibitors before performing surgery, when possible, for spinal neurofibromas. Thus, patients who meet the identified indications for resection should first be evaluated for candidacy in receiving MEK inhibitors if the presentation is not emergent.…”
Section: Discussionmentioning
confidence: 99%
“…Syndromic PNST affect young adults and children and are generally present in multiple localizations, including several subcutaneous lesions; although it is a rare subgroup, malignant PNST are more frequent in syndromic diseases than sporadic conditions. Neurofibromas are mainly related to neurofibromatosis type 1 (NF1), and they present the risk of malignant transformation into aggressive and infiltrative sarcomas ( 7 , 8 ), with severe morbidity and also mortality ( 9 ). The role of adjuvant radiotherapy and traditional chemotherapy remains unclear for such tumors.…”
Section: Introductionmentioning
confidence: 99%